GE_GERICHTE P/7760/2021 vom 8. Dezember 2021 - GE Cour de justice (2021)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;CONSENTEMENT DU LÉSÉ;NÉGLIGENCE;FAUTE;LÉSION CORPORELLE PAR NÉGLIGENCE | CPP.310; CP.125; CP.12